2021
DOI: 10.15388/infedu.2021.19
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Informatics Gap between School and University with the InfoSukces Contest

Abstract: In Poland, talent development is organized mainly outside or alongside the educational system. A large number of privately funded informatics contests and extra-curricular talent development programs for highly motivated students are available. However, traditional competitions also exist including national informatics Olympiads and competitions mainly supported by the Ministry of Education. In particular, we stimulate interest in informatics by organizing the annual nationwide InfoSukces contest. This contest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Future research should take this issue into account with a greater sample size. Note that, now, this policy (concerning six-year-olds starting school) has been abandoned in Poland, and six-year-olds learn in pre-schools, while only seven-year-olds enter the first year of primary school [45].…”
Section: Eduball and Motor Skillsmentioning
confidence: 99%
“…Future research should take this issue into account with a greater sample size. Note that, now, this policy (concerning six-year-olds starting school) has been abandoned in Poland, and six-year-olds learn in pre-schools, while only seven-year-olds enter the first year of primary school [45].…”
Section: Eduball and Motor Skillsmentioning
confidence: 99%
“…They showed how digital media and literacy are being used by primary school students and teachers. Panskyi et al showed how active learning methods, especially gamebased learning, could bridge the gap between schools and universities [44,45]. Moreover, the authors demonstrated the significance of implementing a digital game-based learning approach in out-of-school education to stimulate the creative and innovative learning and teaching of Polish primary school students.…”
Section: A Polish Perspective Beyond Stem/steam Approachesmentioning
confidence: 99%
“…A large number of informatics competitions, contests, summer schools, Olympiads, and extracurricular talent development programs for highly motivated students are available. A large number of traditional competitions, including national Olympiads or competitions for young researchers and engineers, which are mainly supported by the Ministry of Education could boost and accelerate the informatics skills of talented students [3]. However, due to the COVID-19 pandemic, all primary school students are forced to stay at home, and teachers, headmasters and organizers of out-of-school activities changed the formula of the previously traditional informatics education to the version with the use of the Internet.…”
Section: Introductionmentioning
confidence: 99%